Decentralisation in Kenya: the governance of governors*. Issue 1 (9th February 2016) - Cheeseman, Nic; Lynch, Gabrielle; Willis, Justin
Abstract: Kenya's March 2013 elections ushered in a popular system of devolved government that represented the country's biggest political transformation since independence. Yet within months there were public calls for a referendum to significantly revise the new arrangements. This article analyses the campaign that was led by the newly elected governors in order to understand the ongoing disputes over the introduction of decentralisation in Kenya, and what they tell us about the potential for devolution to check the power of central government and to diffuse political and ethnic tensions. Drawing on Putnam's theory of two-level games, we suggest that Kenya's new governors have proved willing and capable of acting in concert to protect their own positions because the pressure that governors are placed under at the local level to defend county interests has made it politically dangerous for them to be co-opted by the centre. As a result, the Kenyan experience cannot be read as a case of 'recentralisation' by the national government, or as one of the capture of sub-national units by 'local elites' or 'notables'. Rather, decentralisation in Kenya has generated a political system with a more robust set of checks and balances, but at the expense of fostering a new set of local controversies that have the potential to exacerbate corruption and fuel local ethnic tensions in some parts of the country.